2005
DOI: 10.1371/journal.pmed.0030019
|View full text |Cite
|
Sign up to set email alerts
|

Are Racial and Ethnic Minorities Less Willing to Participate in Health Research?

Abstract: BackgroundIt is widely claimed that racial and ethnic minorities, especially in the US, are less willing than non-minority individuals to participate in health research. Yet, there is a paucity of empirical data to substantiate this claim.Methods and FindingsWe performed a comprehensive literature search to identify all published health research studies that report consent rates by race or ethnicity. We found 20 health research studies that reported consent rates by race or ethnicity. These 20 studies reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
586
10
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 690 publications
(650 citation statements)
references
References 53 publications
42
586
10
2
Order By: Relevance
“…However, the findings are consistent with a small number of more recent studies that document a willingness to participate among racial and ethnic minorities 37, 38, 39. This study adds to the growing body of literature suggesting barriers beyond willingness 37, 38, 39. Specifically, the paradoxical findings of this study, which showed no difference in the participation rates of racial/ethnic minorities, yet also showed racial/ethnic minorities report both more opportunity and more willingness, needs further exploration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the findings are consistent with a small number of more recent studies that document a willingness to participate among racial and ethnic minorities 37, 38, 39. This study adds to the growing body of literature suggesting barriers beyond willingness 37, 38, 39. Specifically, the paradoxical findings of this study, which showed no difference in the participation rates of racial/ethnic minorities, yet also showed racial/ethnic minorities report both more opportunity and more willingness, needs further exploration.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are inconsistent with several nonpopulation‐based studies that suggest racial/ethnic minorities are less willing to participate 9, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36. However, the findings are consistent with a small number of more recent studies that document a willingness to participate among racial and ethnic minorities 37, 38, 39. This study adds to the growing body of literature suggesting barriers beyond willingness 37, 38, 39.…”
Section: Discussioncontrasting
confidence: 82%
“…43 Reviewing data across 20 studies that reported consent rates by race or ethnicity, Wendler et al reported that minorities were less likely to be recruited, but were equally likely to provide consent when asked to participate in health research studies. 44 This line of evidence seems to indicate that disparities in access to research studies, rather than disparate attitudes and beliefs, underlie the underrepresentation of minorities in research.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing wealth of literature showing that patients from visible minorities are underrepresented in clinical trials [22][23][24]. This has been hypothesized to result from raciallyinfluenced distrust, reduced access to healthcare research, or the failure of clinicians to advertise in a culturally competent manner [25,26]. One large study of 70,000 patients suggests that minorities are willing to enroll in trials, but may lack opportunity to participate.…”
Section: Paternalistic Approachmentioning
confidence: 99%